Tecsun : a utopia ruled with care and love - Xu, Jingyue, (SAGE business cases, 2018)
This case explores the grounds and prospects of the utopian managerial approach of Tecsun (Suzhou) Homes that features paternalistic leadership. It explains the founder's management philosophy with "education" and "enlightenment" as the core, and it demonstrates his leadership style of "paternalistic" in China and "godfather" in the West from multiple perspectives. It further analyzes the influence of the founder's leadership style on employee activation and on the growth mode of the company, offering students insights into the challenges faced by the company and prompts them to think about the issue of sustainability.